Kemampuan Perawatan Diri pada Anak dengan Retardasi Mental - Putu Susy Natha Astini; Ni Kadek Yuni Indrasari; Ni Luh Putu Yunianti Suntari Cakera (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2017)
The Purpose of this research to describe self-care abilities in children with mental retardation in SLB Negeri 1 Gianyar 2017. The research method used is descriptive with cross sectional approach. The study was conducted in April untill May with respondents as many as 35 people. The sampling technique used type of non probability sampling is total sampling. Based on the analysis of data, the ability of self-care for children with mental retardation based on age there were 11 years 11 (31 %), based on gender of respondents most of them male gender 21 (60 %). The Result show, Self-care ability in children with mental retardation in SLB 1 Gianyar as many as 17 (49%) of respondents or mean 55 in the medium category.